Atrium is required in shopping complex / Norsuriany Ibrahim - Ibrahim, Norsuriany (2001)
The Atrium is a peaceful place to sit, meet, and relax amid plants and trees beneath the canopy of the skylight. With the presence of atrium in most of the shopping complexes in Malaysian cities, it has become a unique building form with a wide range of design possibilities. The Atrium at the shopping complex is a censorial, interior, daylit space, which forms part of the organization of a building. By being at a central position, it serves as a place of orientation, thereby bringing spatial coherence to the building. In addition Atrium building with sky light roof can also bring in “daylight*. The potential for an atrium to bring daylight into the centers of a large building is well known, and its energy conservation potential is subject to extensive research. The approach and methodology of this study is basically description in nature. However, emphasis is given to case studies of atrium at selected shopping complexes. The presence of atrium in shopping complexes can be commonly seen in Klang Valley such as at the selected case studies Suria KLCC, Bukit Raja Shopping Complex, and Sungei Wang Plaza. One of the purposes Atrium in shopping complexes is for cultural function that is to modify culture. For economic function, it can modify resources to build, money time, manpower, energy, materials, so as to generate economic return. As shelter, it serves to modify dimate in the building. In fact the Atrium has become useful in carrying out certain urban design strategies in general and the development of shopping complex in particular.